2014
DOI: 10.7897/2230-8407.0507113
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Activity of Avocado Seeds Extracts (Persea Americana Mill.) on T47d Cell Lines

Abstract: Avocado (Persea americana Mill.) is a widely grown plant that had been studied for several activities such as antioxidant and chemopreventive. The aims of this study were to analyze the secondary metabolite compounds contained in avocado seeds and to determine cytotoxic effect from aqueous and ethanolic extracts of avocado seeds against T47D breast cancer cell lines. IC50 value obtained by using MTT assay on aqueous extract, ethanolic extract, and doxorubicin hydrochloride were 560,2 µg/mL, 107,15 µg/mL and 0,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 5 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…Treatment with 200 μ g/mL increased cleavage of caspase-3 and PARP. The differences in effective concentrations used in our study and the others may be related to differences in extract composition or use of different cells [79]. This difference requires further study.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Treatment with 200 μ g/mL increased cleavage of caspase-3 and PARP. The differences in effective concentrations used in our study and the others may be related to differences in extract composition or use of different cells [79]. This difference requires further study.…”
Section: Resultsmentioning
confidence: 83%
“…They found that the triterpenoid fraction and the whole extract had IC 50 values of 80.1 μ g/mL and 99.7 μ g/mL, respectively. Kristanty, Suriawati, & Sulistiyo (2014) found that the cytotoxicity of aqueous and ethanolic extract of avocado seeds inhibited T47D breast cancer cell line with IC 50 values of 560.2 μ g/mL and 107.2 μ g/mL, respectively [9].…”
Section: Introductionmentioning
confidence: 99%
“…Avocado seed had a broad spectrum antibacterial activity, a selective antifungal activity and an overriding activity against Aspergilus niger [8]. Dennis et al [36], reported that, ethanol extract of avocado seed has an antibacterial effect in vitro against Porphyromonas gingivalis with 50% -60%.…”
Section: Egbuonu Et Al Reported That the Avocado Seed Extract (Ase)mentioning
confidence: 99%
“…For example, in America (particularly Latin America), various parts of avocado plants have been used as folk medicine against coughs, bruising, dysentery, diarrhea, wound healing, and hypertension [11]. In addition, the characterization of phenolic components and antioxidant activity of hydroethanolic extracts of avocado skin and seed have demonstrated the predominance of compounds belonging to the group of flavonoids, proanthocyanidins, and hydrocinnamic acids, which have been related with a decrement of the different diseases mentioned above [12,13,14]. Although industrial applications of avocado leaves were not found in the literature, Araújo et al [15] reported several nutritional and functional properties of avocado by-products including avocado leaf extracts as antimicrobial agents.…”
Section: Introductionmentioning
confidence: 99%